Pengaruh intervensi teknik perlekatan (latch-on) pada saat Di ruang postpartum terhadap frekuensi pemberian asi Tanpa mp-asi selama 3 minggu pertama kelahiran - Tri - Sumaryani; Riri - Novayelinda; Sofiana - Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research is to determine the effect of intervention about latch-on technique in postpartum ward on the frequency of breastfeeding without complementary feeding in the first 3 weeks of birth. The design of this research is